Os efeitos de alterações ambientais sobre a produção de Jaraquis (Semaprochilodus Spp) desembarcados na cidade de Manaus - AM - (:unkn) unknown (Universidade Federal do Amazonas, 2016)
This work aimed to analyze the existence of links between environmental factors and fishing activity, stock fishing and fishing landings using the modeling of ecosystems and understand the effects of environmental processes on the chosen variables. In this research we were searched secondary data time series on environmental data - deforestation, the Amazon River flow and air temperature, fish stocks, fish production of the two species jaraquis by competent bodies. All this information was allocated to the power of the final model with the help of Stella software. Each variable is represented by a symbol in the Stella, which was inserted into the functional relationship between the variables (external and state), such as: graphic functions, trigonometric and logical. The simulation results showed optimistic and pessimistic scenarios about the influence of deforestation and the increase of temperature on fish stocks showing decline in these tested over the months. In this model were performed four types of simulations in order to verify the behavior of the fish stocks in a systems change situation
Keywords: Alterações Ambientais; Produção Pesqueira; Atividade pesqueira; Modelagem ecológica; CIÊNCIAS AGRÁRIAS: RECURSOS PESQUEIROS E ENGENHARIA DE PESCA